Technicality, humanity and spirituality --- 3-level multi-dimensional proactive services toward lifelong learning - Gong, Lidu (Qualitative and Quantitative Methods in Libraries, 2017)
This qualitative research explores ‘full service’: 3-level approaches to library services - Technicality, humanity and spirituality. The aim is make librarians aware of the necessity of and pathways to changes in library services. Three metaphors are used to illustrate the proposed changes of service mode - fishing over fish; people over things; and heart over head – in response to the 3-level services respectively. At technical level, service mode changes from reactive towards proactive, from transactional towards interactive, from verbally instructive towards tactile/kinaesthetic, and from information acquisition towards skill training. At humanistic level, changes swop from responsive towards facilitative, from cognitive towards affective, from informative towards transformative, from ‘impartially’ data-geared towards personalised client-centred, and from ‘closure-oriented’ towards ‘step-stone-seeking’. At spiritual level, changes switch from one-off towards follow-up, from dismissive towards reflective, and from dutybound towards passion-driven. Librarians need to scaffold patrons’ learning mode from accumulative towards creative, from extrinsically-motivated towards intrinsically driven.